2017
DOI: 10.1002/stem.2565
|View full text |Cite
|
Sign up to set email alerts
|

Modelling IRF8 Deficient Human Hematopoiesis and Dendritic Cell Development with Engineered iPS Cells

Abstract: Human induced pluripotent stem (iPS) cells can differentiate into cells of all three germ layers, including hematopoietic stem cells and their progeny. Interferon regulatory factor 8 (IRF8) is a transcription factor, which acts in hematopoiesis as lineage determining factor for myeloid cells, including dendritic cells (DC). Autosomal recessive or dominant IRF8 mutations occurring in patients cause severe monocytic and DC immunodeficiency. To study IRF8 in human hematopoiesis we generated human IRF82/2 iPS cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…Langerhans cells) is less clear. However during the last years it is shown that iPSC can be differentiated into several types of immune cells; T-lymphocytes, macrophages, granulocytes, erythrocytes and dendritic cells [5962]. More research is needed to look into the differentiation of iPSC towards skin specific Langerhans cells.…”
Section: Introductionmentioning
confidence: 99%
“…Langerhans cells) is less clear. However during the last years it is shown that iPSC can be differentiated into several types of immune cells; T-lymphocytes, macrophages, granulocytes, erythrocytes and dendritic cells [5962]. More research is needed to look into the differentiation of iPSC towards skin specific Langerhans cells.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of DCs in the initiation of immune responses among antigen-naïve T cells has fueled interest in iPSCs as a renewable and scalable source of rare DC subsets with desirable properties not normally vested in moDCs, 3,4 the population most frequently used in clinical trials. 2 ( Figure 1B,D), a phenotype equally evident among ipDCs of mouse 37 and human origin.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although such trials have demonstrated only limited efficacy, induced pluripotent stem cells (iPSCs) may provide an unlimited source of previously inaccessible subsets of DCs, such as plasmacytoid DCs 3 and CD141 + DCs displaying superior capacity for the cross-presentation of TAAs. 4 Unlike moDCs, such a novel source is amenable to scale-up, quality control and genome editing, 3,5 making it attractive for downstream therapeutic applications. 6 Nevertheless, iPSC-derived DCs (ipDCs) appear arrested at a stage of development more reminiscent of a fetal rather than an adult phenotype, a finding common to many cell types differentiated from a pluripotent source, including hepatocytes, 7 cardiomyocytes, 8 and forebrain neurons.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Additionally, iPSCs and embryonic stem cells (ESCs) are readily subjected to genome engineering by CRISPR/Cas9 to precisely introduce or repair oncogenic mutations. 26,28,29 We report here on the generation of KIT D816V iPSCs from SM patients. SM-derived KIT D816V iPSCs differentiated into hematopoietic progenitor cells (HPCs) and MCs with patient-specific features.…”
Section: Introductionmentioning
confidence: 99%